Nitrogen Biogeochemistry of an Urban Rooftop Farm - Harada, Yoshiki; Whitlow, Thomas H.; Templer, Pamela H.; Howarth, Robert W.; Walter, M. Todd; Bassuk, Nina L.; Russell-Anelli, Jonathan (Frontiers in Ecology and Evolution, 2018)
Intensive agriculture represents a recent extension of green roof technology. Perceived ecosystem services provided by rooftop farming include stormwater management and the production of affordable and nutritious vegetables for local consumption. However, intensive agriculture can increase nutrient loads to surface water, yet there is little empirical data from full-scale operational rooftop farms. This study reports the N balance and N management efficiency of the Brooklyn Grange Navy Yard Farm, a 0.61-ha farm atop an 11-story building in New York City USA. We monitored atmospheric N deposition, soil N concentration, N output by harvest, N leaching from soil, and drainage N output, in addition to estimating net N mineralization and the N load to sewers during the combined sewer overflows. We found that the annual drainage N output was 1100% of the atmospheric bulk N deposition, and was 540% of the estimated total atmospheric N deposition, which makes the Brooklyn Grange a net N source in the urban environment. Annual N leaching from soil was 97% of fertilizer N input, and the efficiency of N management can be lower than in conventional vegetable production. For the Brooklyn Grange to integrate stormwater management and intensive agriculture, it will be important to use soil with greater water holding capacity within the range of readily available water, and to recycle drainage. This case study shows how the intensification of agriculture on rooftops should be managed for both the yield and quality of crops and to reduce N loss to storm drains, which affects aquatic ecosystems and water quality.